Ca2+ signaling and metabolic stress-induced pancreatic β-cell failure - Magnuson, Mark A.; Osipovich, Anna B. (Frontiers in Endocrinology, 2024)
Early in the development of Type 2 diabetes (T2D), metabolic stress brought on by insulin resistance and nutrient overload causes β-cell hyperstimulation. Herein we summarize recent studies that have explored the premise that an increase in the intracellular Ca 2+ concentration ([Ca 2+ ]i), brought on by persistent metabolic stimulation of β-cells, causes β-cell dysfunction and failure by adversely affecting β-cell function, structure, and identity. This mini-review builds on several recent reviews (1-5) that also describe how excess [Ca 2+ ]i impairs β-cell function.